Perbandingan Pendapatan Pedagang Sayuran di Dua Pasar Tradisional di Kecamatan Bandungan, Kabupaten Semarang - Aziz, Abdul; Prihtanti, Tinjung Mary (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Jimbaran and Bandungan markets are two large traditional markets around Semarang Regency. Jimbaran market is a village market that residents use for trading, while Bandungan market is a market close to tourist areas. The research objective is to analyze the difference in income earned by vegetable traders at Jimbaran market and Bandungan market, Bandungan District, Semarang Regency. This research uses a quantitative approach with survey techniques to collect data through interviews with 15 vegetable traders in the Jimbaran market and 15 in the Bandungan market. Respondents were selected using purposive sampling: traders trading for at least five years sold four types of vegetables (carrots, tomatoes, cabbage, potatoes) and did not sell necessities. The analysis technique uses revenue analysis formulas, costs, income, and independent t-tests. The results of the research found that there was a significant difference between the income of vegetable traders in the Jimbaran market and those selling in Bandungan, shown by a significance value of 0.00, where the income of traders in the Bandungan market is higher than the Jimbaran market. The average income of vegetable traders in the Jimbaran market is IDR. 861.933,33 per week, while vegetable traders in the Bandungan market earn an average income of IDR 1.584.333,33 per week. The difference in income between the two is Rp. 722.400,00. The differences in income are partly due to the influence of the location of the Bandungan market near tourist areas.